2020
DOI: 10.1016/j.ijcard.2019.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of the high right atrium to coronary sinus conduction time predicts the recurrence of atrial fibrillation after radiofrequency catheter ablation

Abstract: Background: The impact of intra-atrial conduction delay on the recurrence of atrial tachyarrhythmia after radio frequency catheter ablation (RFCA) has not been fully elucidated. Methods: We retrospectively analyzed 155 AF patients who were sinus rhythm at the start of RFCA. The conduction time from the onset of the earliest atrial electrogram at the high right atrium (HRA) to the end of the latest electrogram at the coronary sinus (CS) during sinus rhythm was defined as HRA-CS conduction time. Pulmonary vein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…17 In another study performed in patients undergoing catheter ablation, right atrial conduction time was significantly associated with the occurrence of recurrent AF. 29 That study confirms our finding of increased conduction time as a robust, single point measurement, associated with the risk of recurrent AF. Moreover, we demonstrated that LAECT provides additional information on the arrhythmogenic substrate, beyond clinical characteristics and left atrial size, with prognostic implications for AF recurrence.…”
Section: Left Atrial Epicardial Conduction Timesupporting
confidence: 89%
See 1 more Smart Citation
“…17 In another study performed in patients undergoing catheter ablation, right atrial conduction time was significantly associated with the occurrence of recurrent AF. 29 That study confirms our finding of increased conduction time as a robust, single point measurement, associated with the risk of recurrent AF. Moreover, we demonstrated that LAECT provides additional information on the arrhythmogenic substrate, beyond clinical characteristics and left atrial size, with prognostic implications for AF recurrence.…”
Section: Left Atrial Epicardial Conduction Timesupporting
confidence: 89%
“…This seemingly contradictory finding may be the result of more preferential conduction along, compared with parallel to the fibres in more fibrotically remodelled atria, that is, of more anisotropy 17. In another study performed in patients undergoing catheter ablation, right atrial conduction time was significantly associated with the occurrence of recurrent AF 29. That study confirms our finding of increased conduction time as a robust, single point measurement, associated with the risk of recurrent AF.…”
Section: Discussionsupporting
confidence: 70%
“…Recent investigations have provided additional evidence to link IAC disturbance with AF. Kanemaru et al ( 11 ) measured conduction time between the high RA and the CS during SR as a surrogate of IAC time, and it was a predictor of AF recurrence after catheter ablation. Spies et al ( 10 ) focused on mechanisms of PQ interval prolongation in patients with atrial arrhythmias, and right IAC delay estimated by His bundle recording was a underlying cause in patients with AF and atrial flutter compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high interest in CS EGMs during AF, little or no attention has been paid to CS function during SR and its modification after CA procedures. Prolonged conduction time measured between EGMs from RA and CS in recordings acquired before CA of PVs and complex EGMs has shown high predictive power for atrial tachyarrhythmia occurrence [ 29 ]. Moreover, in CA of atrial flutter, fractionation in the EGMs of CS can predict the incidence of AF [ 30 ].…”
Section: Introductionmentioning
confidence: 99%